INTERACTION OF THE Fe/γ-Al2O3 CATALYTIC SYSTEM WITH PROBE MOLECULES IV. STUDY OF THE INTERACTION OF HYDROGEN WITH γ-Al2O3 OXIDE AND THE Fe/γ-Al2O3 SYSTEM - Brodskiy A.R.,; Grigoriyeva V.P.,; Komashko L.V.,; Nurmakanov Y.Y.,; Chanysheva I.S.,; Shapovalov A.A., (Academic Scientific Journal of Chemistry, 2020)
The work is devoted to the study of the interaction of heterogeneous catalytic systems with adsorbed molecules. The results of the interaction with a hydrogen of -Al2O3 oxide and the Fe/-Al2O3 system using IR spectroscopy, methods of temperature programmed desorption and temperature programmed reduction by hydrogen are presented. An ability of the system to adsorb and activate the initial H2 probe molecule was defined and an assessment of the active (adsorption) centers was made. Various adsorption centers were detected during their interaction with hydrogen in the temperature range 293-773K on the surface of both γ-Al2O3 oxide and the Fe/γ-Al2O3 system using IR spectroscopy. The relative intensity of the absorption bands corresponding to these centers depends on the temperature of interaction with hydrogen. The adsorbed hydrogen is desorbed in the form of two peaks on the temperature scale from the -Al2O3 surface and in the form of three peaks from the surface of the Fe/γ-Al2O3 system. The appearance of additional desorption peaks for the Fe/γ-Al2O3 system is associated with iron deposited on alumina. It was concluded that on the surface of -Al2O3 oxide and the Fe/γ-Al2O3 system, there are adsorption centers that differ in energy characteristics (binding energy). Moreover, these characteristics may also depend on the percentage of the iron-containing component on the surface of aluminum oxide. Two adsorption peaks are observed on the temperature scale for -Al2O3 oxide and in the case of the Fe/γ-Al2O3 system, in addition to two adsorption peaks, a desorption peak is also observed using the TPR method of hydrogen. -Al2O3 oxide and the Fe/-Al2O3 system contain different states of metal oxide forms, since several maxima are clearly distinguishable on the TPR curves of hydrogen which indicates the reduction of particles of various compositions.